2015
DOI: 10.1039/c4cp04593a
|View full text |Cite
|
Sign up to set email alerts
|

Photodesorption of water from rutile(110): ab initio calculation of five-dimensional potential energy surfaces of ground and excited electronic states and wave packet studies

Abstract: In this paper, we report on our results concerning the interaction of water with titanium dioxide in its rutile modification. The (110) surface is modelled by an embedded Ti9O18Mg7(14+) cluster. We present up to five-dimensional potential energy surfaces for the water molecule on this surface and include the dissociation of one hydrogen atom. The electronic ground state as well as one electronically excited state is included. To deal with the multi-configurational character of the wave function, we use the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
1
3
1
Order By: Relevance
“…For long resonance lifetimes of the CT state of about 240 fs, this rate converged to a value of 85%, irrespective of the vibronical excitation. In comparison with previous simulations on the H 2 O/r-TiO 2 (110) system, which exhibit converged photodesorption probabilities of 82%, 41 both modifications presumably exhibit similar properties with regard to this prototype of a photoreaction. However, for r-TiO 2 (110), the velocity distribution of the desorbed molecules revealed a sharp peak at 4600 m s −1 , whereas in our study, a-TiO 2 (101) features a bimodal distribution with much smaller velocities of 1650 and 2000 m s −1 .…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…For long resonance lifetimes of the CT state of about 240 fs, this rate converged to a value of 85%, irrespective of the vibronical excitation. In comparison with previous simulations on the H 2 O/r-TiO 2 (110) system, which exhibit converged photodesorption probabilities of 82%, 41 both modifications presumably exhibit similar properties with regard to this prototype of a photoreaction. However, for r-TiO 2 (110), the velocity distribution of the desorbed molecules revealed a sharp peak at 4600 m s −1 , whereas in our study, a-TiO 2 (101) features a bimodal distribution with much smaller velocities of 1650 and 2000 m s −1 .…”
Section: Discussionsupporting
confidence: 59%
“…In addition, vibronically excited wavepackets do not significantly alter this finding and only show a small decrease in this probability of 81%. In comparison to previous work on the photodesorption of H 2 O from r-TiO 2 (110) by Mitschker et al, which found a converged desorption probability of 82% for large resonance lifetimes, both materials presumably exhibit similar properties regarding the photodesorption dependence on the lifetime of the CT state.…”
Section: Resultscontrasting
confidence: 42%
See 2 more Smart Citations
“…To verify this, we used cutoff optical filters with the UV source and did not observe any CO photodesorption for photon energies below the TiO 2 band gap (∼3.1 eV), the threshold for the electron–hole generation. Direct photoexcitation and desorption of the adsorbed CO molecule requires more than a 6 eV photon energy, which cannot be achieved in our experiments with a mercury lamp source.…”
mentioning
confidence: 97%